Contribution of Educational and Economic Factors to HDI Scores of Districts/Cities in East Java: A Multiple Linear Regression Study - Giovani Septio; Alifa Syauqi Hatami; Luthfiani Luthfiani; Vera Maya Santi (Dinasti International Journal of Education Management and Social Science, 2025)
The Human Development Index (HDI) is a strategic indicator that reflects the quality of life, achievements of society, particularly in the domains of education and economy. This study aims to analyze the contribution of educational and economic factors to the variation in HDI scores across districts and municipalities in East Java Province. A quantitative approach was employed using multiple linear regression analysis. The independent variables include the number of senior high schools, the student–teacher ratio in senior high schools, the Net Enrollment Rate (NER) at the senior high school level, the poverty rate, and per capita expenditure. The dependent variable is the Human Development Index (HDI). Data were obtained from the 2023 publication of Statistics Indonesia (BPS), covering 38 districts/municipalities in East Java Province. The results indicate that the educational and economic factors significantly contributing to HDI are the NER, poverty rate, and per capita expenditure, while the number of senior high schools and student–teacher ratio show no significant contribution. The regression model strongly explains the proportion of HDI variance with a high R-square value, making it a reliable basis for formulating regional development policies. This study underscores that interventions aimed at improving educational attainment and strengthening the local economy are key strategies for accelerating human development in East Java. Although the multiple linear regression model used in this study shows strong explanatory power in identifying the educational and economic determinants of HDI across districts and cities in East Java, this model assumes independence between observation units and still cannot explain other indicators that influence HDI in detail. Therefore, future research on HDI indicators could utilise a multilevel or linear mixed modelling framework to achieve a more robust analytical level that could assist policymakers in formulating policies.